Queer(y)ing Indigenous Australian higher education student spaces - Sullivan, Corrinne; Day, Madi (The Australian Journal of Indigenous Education, 2019)
Abstract For many Queer and Gender Diverse (QGD) Indigenous Australian people, there is little to no separation between our queer or gender identity, and our cultural identity. We are increasingly calling upon institutions to consider and cater to our identities and the needs which correlate with such identities. This paper discusses the findings of a project that investigated the ways in which QGD Indigenous Australian students are included, or not, in the Australian higher education space. Our findings suggest QGD Indigenous Australians are often overlooked in these spaces. We explore the consequences for university access, retention and personal impact for this cohort of students.